Evaluasi efektivitas pemilihan umum dalam memperkuat sistem kepresidenan berdasarkan prinsip Pancasila - Laksono, Muhamad Ali Wahyu Dwi (Maliki Interdisciplinary Journal, 2025)
General Elections (Pemilu) are a crucial instrument in realizing democracy in Indonesia based on the values of Pancasila. Elections aim to select leaders and representatives of the people through direct, general, free, confidential, honest, and fair processes. However, the implementation of elections in Indonesia still faces various challenges, such as rampant money politics, political polarization, low political participation, and structural barriers to transparent and effective administration. This article aims to analyze the extent to which Pancasila principles are implemented in elections, identify the obstacles encountered, and formulate strategic steps to improve the effectiveness of elections in strengthening the presidential system in Indonesia. Using a qualitative descriptive approach, this study emphasizes the importance of integrity, transparency, and active public participation in every stage of the election process. It is hoped that consistent implementation of Pancasila values will create high-quality elections and equitable democracy in Indonesia.